PENGARUH MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS VII SMP NEGERI 12 PADANG - Ramadhani, Gusma Suci; Ermanto, Ermanto; Nursaid, Nursaid (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACTÂ The purpose of this research is to describe the influence of modeling problem based learning aided media beamed images the text short story writing skills by the students VII grade SMPNegeri 12 Padang. This type of research is quantitative with experiment method that used is statis design two groups. Based on the results of data analysis it was concluded the following three points.First, the skills of writing the text short story by the students VII grade SMPNegeri 12 Padang using conventional models is located on qualifications is good (76,94). Second, the skills of writing the text short story by the students VII grade SMPNegeri 12 Padang using modeling problem based learning aided media beamed image is located on qualifications is good (82,00). Third, based on the result of uji-t, there is effects of modeling problem based learning aided media beamed images the text story writing skills by the students VII grade SMPNegeri 12 Padang because tscore> ttable(5,62 > 1,70).Â Kata kunci: pengaruh, model problem based learning berbantuan media gambar berseri, teks cerpen